Pengaruh Gaya Belajar dan Sikap Siswa pada Pelajaran Matematika terhadap Hasil Belajar Matematika - Leny Hartati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
This study aims to determine the effect of learning styles and attitudes of students in math on math learning outcomes. The method used is the method Expose Facto. The study sample drawn from a population with affordable proportional random technique, as many as 60 students. The instrument used in this study is a questionnaire instrument to measure learning style variables and variable attitudes of students in math, and test instruments, to measure the outcomes of learning mathematics. The research design used in this study is a 3 x 2 factorial design with three variables consisting of two independent variables, namely cognitive learning styles and attitudes of students in math, as well as the dependent variable, which is the result of learning mathematics. From the data processing obtained the following results: (1) There are differences in mathematics learning outcomes of students who have a visual learning style, auditory and kinesthetic. It is in the show by the price of the F - count of 2,494 with a probability of 0.047 sig (sig < 0.05) at significance level ? = 5 %. (2) The results of the mathematical learning of students who have a positive attitude at a higher math than students who have a negative attitude on math. It is in the show by the price of the F - count of 3,124 with a probability of 0.018 sig (sig < 0.05) at significance level. (3) There is no interaction between the learning styles of students in math attitudes toward math learning outcomes. It is in the show by the price of the F - calculated interaction probability value was 1.621 while sig. for interaction (learning styles * attitude of students in math) of 0.140 (sig > 0.05).